From Single-Chain Polymeric Nanoparticles to Interpenetrating Polymer Network Organogels: A One-Pot Fabrication Approach - Daglar, Selin; Balta, Demet Karaca; Temel, Binnur Aydogan; Temel, Gokhan (MDPI, 2025)
In this study, we developed a novel one-pot synthesis method to fabricate well-defined single-chain polymeric nanoparticles (SCNPs) integrated with interpenetrating polymer network (IPN) systems. The synthesis process involved an initial intramolecular crosslinking of poly(methyl methacrylate-co-glycidyl methacrylate) to form SCNP followed by intermolecular crosslinking to produce single-chain nanogel (SCNG) structures. In addition, the achieved single-chain polymeric nanoparticle was subsequently incorporated into an IPN structure through urethane bond formation and a Diels-Alder click reaction involving furfuryl methacrylate (FMA) and bismaleimide (BMI). The thermal properties, swelling behaviors, and morphologies of the resulting SCNP-IPN systems were investigated. This work presents a novel strategy that integrates the single-chain folding concept with IPN systems, providing a promising platform for the development of robust and functional polymeric materials with potential applications in advanced materials science.
Keywords: single-chain polymeric nanoparticles; chain folding; interpenetrating polymer network; organogel; Polymer Science